Evaluation of the Properties of the Polymer Composition Using a Fuzzy Analysis of the Formulation - Germashev, I.V.; Derbisher, E.V.; Mashihina, T.P. (2019 International Multi-Conference on Industrial Engineering and Modern Technologies (FarEastCon), 2019)
The task of assessing the quality of the polymer composition is considered. The main role in the formation of requirements for polymers is played by the demands of consumers and the technology of their production when creating polymer compositions. Assessment is proposed to carry out by calculating the influence of ingredients on the properties of the polymer composition. In multicomponent systems, this effect is rather difficult to assess due to the indefinite interaction of the ingredients. It is proposed to use a fuzzy analysis to account for such uncertainties when evaluating each component of the polymer composition. A specific example and solution of the problem by this example is given. The results of the study allow the use of information technology research and production activities of a chemical technologist in terms of assessing the consumer quality of polymer compositions for sound decision making when choosing the optimal composition of composite materials. Baseline data is presented in the form of fuzzy numbers, which allows you to abstract from the subject area and go into a multidimensional description of information systems. In particular, the calculation of the index of the influence of each additive on the polymer composition in relation to the requirements imposed allows the use of relative dimensionless quantities to describe the properties of the system. The cumulative evaluation of the properties of the system was carried out according to the principle of weighted voting. The resulting value reflects the degree of compliance of the polymer composition of the set to the requirements as a whole.